Caffeine May Abrogate LPS-Induced Oxidative Stress and Neuroinflammation by Regulating Nrf2/TLR4 in Adult Mouse Brains - Badshah, Haroon (Biomolecules, 2019)
Herein, we assayed the antioxidant and anti-inflammatory potential of caffeine in a lipopolysaccharide (LPS)-injected mouse model of neurodegeneration and synaptic impairment. For this purpose, LPS was injected for two weeks on an alternate-day basis (250 µg/kg/i.p. for a total of seven doses), while caffeine was injected daily for four weeks (30 mg/kg/i.p/four weeks). According to our findings, there was a significant increase in the level of reactive oxygen species (ROS), as evaluated from the levels of lipid peroxidation (LPO) and ROS assays. Also, we evaluated the expression of nuclear factor erythroid-2-related factor 2 (Nrf2) and the enzyme hemeoxygenase 1 (HO-1) in the mouse groups and found reduced expression of Nrf2 and HO-1 in the LPS-treated mice brains, but they were markedly upregulated in the LPS + caffeine co-treated group. We also noted enhanced expression of toll-Like Receptor 4 (TLR4), phospho-nuclear factor kappa B (p-NF-kB), and phospho-c-Jun n-terminal kinase (p-JNK) in the LPS-treated mice brains, which was significantly reduced in the LPS + caffeine co-treated group. Moreover, we found enhanced expression of Bcl2-associated X, apoptosis regulator (Bax), and cleaved caspase-3, and reduced expression of B-cell lymphoma 2 (Bcl-2) in the LPS-treated group, which were markedly reversed in the LPS + caffeine co-treated group. Furthermore, we analyzed the expression of synaptic proteins in the treated groups and found a marked reduction in the expression of synaptic markers in the LPS-treated group; these were significantly upregulated in the LPS + caffeine co-treated group. In summary, we conclude that caffeine may inhibit LPS-induced oxidative stress, neuroinflammation, and synaptic dysfunction.